It is an algebraic expression in the form of: b+14
b + 1 is b plus 1 as an algebraic expression.
It is: b+b+b = 3b
The answer is b+1. Therefore the algebraic expression for this is b+1
The value of a + b depends on the values of the individual variables.The expression a + b cannot be simplified.
The expression (a+b) + (a-b) can be rewritten as a + b + a - b = 2a.There is no need to use absolute value.
It is the same as: 3b+4c which is an algebraic expression
It is b + 9.
a + b + 4 is in its simplest form.
The expression is: (4a+b)/(2a-5b)
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
It's simple, x+a = b is the expression
2a+b=2a+b. Without a value for a and b, the expression has no value.
(b + 3)(a + c)
int x = 2 * (a + b);
It could be a^3 + b or (a + b)^3, depending on the context.
(2a + b)(2c + d).
When factored it is: 12(A+b)
According to the Law of Absorption, A+(A*B) = A. Boolean B is "absorbed" by A.Similarly, A*(A+B) = A.
That expression has no answer, simply because it's not a question.